Characterisation of simple sequence repeats in the Asian Seabass,Lates calcarifer by random sequencing - Pan, Pan Chong; Adura Mohd. Adnan,; Kiew, Lian Wan (Universiti Kebangsaan Malaysia, 2011)
In recent years, there has been considerable interest in simple sequence repeats (SSRs) particularly as molecular markers with applications in many different fields. We have carried out an effort to identify and analyse SSRs in the genome of the Asian seabass, Lates calcarifer by random sequencing. Genomic DNA was isolated from the muscle tissue of L. calcarifer, sheared by nebulisation and ligated into plasmid vector. Recombinant clones were selected randomly from the genomic libraries constructed. Subsequently, plasmid DNA was extracted and subjected to one-pass sequencing. A total of 4175 random sequences, also known as genome survey sequences (GSSs), with a total length of 1.7 Mb was generated. Screening of the whole L. calcarifer GSS data set allowed for the identification of a total of 151 perfect (100% similarity) SSRs. These SSR consensus patterns spread over a wide range of size (1 to 226 bp). The most frequent consensus pattern is dinucleotide, which represents 60% of all SSRs identified. The dinucleotides (AC)n, (AT)n and (AG)n were also found to occur frequently in the L. calcarifer genome. Sequence comparison between L. calcarifer and other fish species showed variation in repeat content, indicating the different ways in which repeats may evolve in the genome of these species. Data generated from this random sequencing of the L. calcarifer genome should serve as a valuable resource for further studies of this organism